BEBERAPA TITIK KRITIS MURABAHAH DALAM FATWA DSN - Husni Husni (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2017)
A reality that can not be denied is the dominance of murabaha as a financing contract in sharia financial institutions. The dominance is also included in the number of fatwas that regulate murabaha. The number of fatwas, indirectly implies the number of "defective" holes that must be covered in the use of murabaha contracts to make it appear legitimate in syar'i. Keywords: Murabahah, Hilah, Riba, Akad